Preparation of core-shell polymer supports to immobilize lipase B from Candida antarctica: Effect of the support nature on catalytic properties - Cunha, Aline G.; Besteti, Marina D.; Manoel, Evelin A.; Silva, Angelo A.T. da; Almeida, Rodrigo V.; Simas, Alessandro B.C.; Fernández-Lafuente, Roberto; Pinto, José Carlos; Freire, Denise Maria Guimarães (Journal of Molecular Catalysis B: Enzymatic, 2014)
Core–shell supports have been prepared and utilized to immobilize lipase B from Candida antarctica. The hydrophobic nature of the supports permitted to immobilize the enzyme via interfacial activation at low ionic strength. Different supports were prepared having different hydrophobicity and crosslinking degree, and compared to the commercially available. Accurel MP 1000 (hydrophobic macroporous polymer of propylene) is a commercial support described as advantageous in different circumstances and it was used as comparative control in the process of immobilization. The immobilized lipase preparations were evaluated in the hydrolysis of p-nitro-phenyl laurate and the esterification of oleic acid with ethanol. On the kinetic resolution of (±)-1,2-O-isopropylidene-3,6-di-O-benzyl-myo-inositol, vinyl acetate was used as activated acyl donor. Results were very diverse, as the lipase properties may be easily tuned via immobilization, and some of the supports permitted to obtain activities even a two fold factor higher than the same amount of lipase immobilized in Accurel MP 1000. Moreover, in many instances, the loading of the support with enzyme produced reduced total activity in some reactions while not in other. This was explained by changes in the physical properties of the support surface that may alter the entry of substrates. Supports PS-co-DVB/PS-co-DVB 25% and PMMA-co-DVB/PMMA-co-DVB 25% presented very good features to immobilize CALB. This work was supported by grants from Petrobras, CNPq and CTQ2009-07568 from Spanish Ministerio de Ciencia e Innovación. Peer Reviewed